Editorial - Zhiyuan Li; Santosh Pande (ACM Transactions on Embedded Computing Systems, 2009)
Publisher Note: This Guest Editorial by Li and Pande describes a number of related articles originally intended as a special issue but which were published in earlier issues as follows: Auerbach et al., "Low-Latency Time-Portable Real-Time Programming with Exotasks" , appears in TECS 8(2) Article 15 DOI 10.1145/1457255.1457262 Murray et al., "Code Transformation and Instruction Set Extension" , appears in TECS 8(4) Article 26 DOI 10.1145/1550987.1550989 Ahn and Paek, "Register Coalescing Techniques for Heterogeneous Register Architecture with Copy Sifting" , appears in TECS 8(2) Article 16 DOI 10.1145/1457255.1457263 Yan and Zhang, "Analyzing the Worst-Case Execution Time for Instruction Caches with Prefetching" , appears in TECS 8(1) Article 7 DOI 10.1145/1457246.1457253